Seed Viability, Seedling Growth and Yield in White Guinea Yam - Norman, Prince E.; Danquah, Agyemang; Asfaw, Asrat (MDPI, 2020)
The yam is an economic tuber crop utilized for food, feed, and various industrial applications. Botanical seed viability, seedling growth, and development are among factors that influence plant population dynamics, development, structure, and sustainability. However, little is known about seed viability, growth, and yield potential of seed-progenies developed using different mating designs. This study assessed seed germination, seedling growth, and yield traits in seed-progenies developed using North Carolina I (NC-1) and polycross mating designs. For this, seed germination and seedling nursery trials established using seed-progenies from different yam crosses were used. Results revealed that days to first seed germination (DAYFG), days to 50% germination (DAYSG), coefficient of velocity of germination, seed emergence speed (SES), germination index, final germination percent, and seedling vigor index significantly (p < 0.05) varied within and among NC-1 and PC-derived families. The mean days to first seed germination (DFSG) and DAYSG seed-progenies of NC-1 were significantly lower than the polycross progenies. Moreover, the seedling-progenies from the polycross produced a higher number of stems and more elongate tubers than those originated from the NC-1 mating. Progenies of family TDr1687 from a polycross mating were among the families that had the highest stem number (2.2), longest tuber (7.5 cm), and widest tuber (2.8 cm). The inter-family means of both NC-1 and polycross had a non-significant variation for mean tuber weight per plant. Our results suggest the relevance of seed germination and seedling attributes for selection of superior progenies at the early generation stage trials in yam breeding.
Agronomy 2021, Volume 11
Keywords: Pangirayi B. Tongoona; Eric Y. Danquah; Robert Asiedu; Dioscorea rotundata; hybrid progeny; seed viability; seedling traits; mating systems; Agriculture; University of Ghana